2009
DOI: 10.1002/biot.200800204
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of phenol by a novel partitioning bioreactor using cow dung microbial consortia

Abstract: A bioreactor has been designed and developed for partitioning of aqueous and organic phases with a provision for aeration and stirring, a cooling system and a sampling port. The potential of a cow dung microbial consortium has been assessed for bioremediation of phenol in a single-phase bioreactor and a two-phase partitioning bioreactor. The advantages of the two-phase partitioning bioreactor are discussed. The Pseudomonas putida IFO 14671 has been isolated, cultured and identified from the cow dung microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Pseudomonas putida IFO 14671 has been isolated, cultured, and identified from the cow dung microbial consortium as a high-potential phenol degrader [49]. …”
Section: Municipal Sludge With Metalsmentioning
confidence: 99%
“…The Pseudomonas putida IFO 14671 has been isolated, cultured, and identified from the cow dung microbial consortium as a high-potential phenol degrader [49]. …”
Section: Municipal Sludge With Metalsmentioning
confidence: 99%
“…In order to investigate some unique microbial source for bioremediation study, animal waste-cow dung has been used as a novel source. The presence of abundant macro and micronutrients provide suitable conditions for microbial growth in the cow dung, which could be an effective source for bioremediation of hazardous wastes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, cow dung was found to be useful in bioremediation of pharmaceutical, pesticides and petrochemical waste [2,[29][30]. Interestingly in Nigeria, cow dung was assessed for aerobic, heterotrophic bacteria and petroleum-utilizing bacteria as well as degradation potential of petroleum-utilizing bacteria isolates [31].…”
Section: Discussionmentioning
confidence: 99%